Acute stress responses of autonomous nervous system, HPA axis, and inflammatory system in posttraumatic stress disorder - von Majewski, Kristin; Kraus, Olga; Rhein, Cosima; Lieb, Marietta; Erim, Yesim; Rohleder, Nicolas (Translational Psychiatry, 2023)
Posttraumatic stress disorder (PTSD) does not only have direct consequences for well-being, but it also comes with a significant risk for severe somatic health consequences. A number of previous studies have pointed to alterations in stress systems in traumatized persons, as well as the inflammatory system, which might be important links in the pathway between trauma, PTSD, and health consequences. The aim of this study was to investigate acute stress responses in PTSD patients compared with healthy controls. Twenty-seven PTSD patients and 15 controls were exposed to the Trier Social Stress Test (TSST), and we measured salivary cortisol, salivary alpha-amylase (sAA), plasma interleukin-6 (IL-6), as well as heart rate and heart rate variability (HRV) at different time points before, during and after the stress test. Results revealed similar stress responses between patients and controls, but lower baseline cortisol levels and higher IL-6 baseline levels in PTSD patients. Increases in sAA stress responses were significantly lower in patients, while sAA concentrations were higher in the PTSD group during intervention. HRV was markedly decreased in patients and showed a significantly blunted acute stress response with a slower recovery after TSST. These results confirm previous findings of marked stress system dysregulations in PTSD and add to the literature on acute stress reactivity in PTSD which appears to show stress system-specific changes. Overall, these results have implications for our understanding of potential risk and resilience factors in the response to trauma.
CRIS-Team Scopus Importer:2023-02-10